A Kénosis Trinitária como manifestação da misericórdia - Meira, André Luiz Bordignon (2017)
Trinitarian kenosis in Christ’s event allows to grasp Church’s practice based in the perichoretic trinitarian relationship of Trinity’s donation in history. The fundamental issue lies within the drama of God and human relationship, where God donates Himself to be near the human being. Church’s practice is then understood as a merciful and loving pastoral. God’ mercy to human being, from Balthasar’s discussion of kenosis and Trinity reveals kenosis as an expression of Trinity’s mercy. Theological reflection allows to search for new paradigms that might address God in our times. This study explored Hans Urs von Balthasar’s theology, especially in his text Misterium Paschale, to study God’s will that, in His kenosis, in each person of Trinity, seeks for human beings in a loving and merciful action. People in our times, despite technological progress, seem to be distant to each other, developing a merciless awareness. Thus, reflections produced by this study search in Balthasar’s theology what is revealed by Christ in His incarnation, death, and resurrection: a lowering of God, kenotic, of a total annihilation of His divinity, to manifest all His Mercy to human person. God, in His freedom, chooses to be present in the drama of human life, despite humanity’s sufferings, and leads the Church to a mystic and merciful practice